An Evaluation of Recent Global Geopotential Models for Strip Area Project in Turkey - Serkan Doganalp (Earth Sciences Research Journal)
The aim of this study is to present the evaluations based on comparisons of geoid heights that are computed from several global geopotential models (GGMs) and the GNSS/levelling data. In this application framework, differences between geoid heights obtained by GGMs and GNSS/levelling were computed. Then, the availability of geoid heights calculated by GGMs for engineering applications were investigated. The Konya-Polatli (Ankara) Express Train Project as a strip area project was chosen as the study area. The length of the project is approximately 210 km and consists of 110 benchmarks that belong to the Turkish National Triangulation Network. In this study a total of 69 GGMs were compared. In order to examine more detail, these models were classified as three groups based on CHAMP, GRACE and GOCE. Each group was evaluated separately and the results were obtained. According to results, the best five models were detected for geoid height differences (NGNSS/lev-Nggm) in terms of standard deviation. These are EIGEN-6c4, EIGEN-GRACE01s, EGM2008, EIGEN-6c3stat and EIGEN-6c2, respectively. Also, geoid heights were obtained using different parametric models. These parametric models were used in order to minimize the impact of the terms of bias, tilt etc. Generally, three, four, five and seven parametric models are used for the least-squares adjustment of the geoid height differences in the literature. Therefore, in this study the geoid heights were calculated for such different parametric models. After the geoid height values were computed from the parametric models, the best global geopotential models in terms of standard deviation were obtained as EIGEN-6c2, EIGEN-6c3stat, EGM2008, EIGEN-6c4 and EIGEN-GRACE01s, respectively.